Evaluation of Ion-pair Formation of Adefovir to Improve Permeation across Artificial and Biological Membranes - Bahar Darsazan; Alireza Shafaati; Afshin Zarghi; Seyed Alireza Mortazavi (Frontiers Media S.A., 2018)
Purpose: Adefovir is an antiviral drug that exhibits high hydrophilic properties and negligible bioavailability (less than 12%). It is only applied in the form of the ester prodrug adefovir dipivoxil (ADV). The oral bioavailability of ADV is limited (32% to 45%) by its low permeability (Class 3) and biological conversion of the prodrug to adefovir. Ion-pair formation is considered as an alternative approach to a covalent prodrug (ADV) to enhance intestinal permeation of adefovir. Methods: The effect of various counter-ions (anionic, cationic and two quaternary ammonium salts) on the lipophilicity of adefovir was investigated by means of the n-octanol/buffer partitioning system, an in vitro transport model (PAMPA) and a biological membrane (everted gut sac). Results: Quaternary ammonium salts, cetylpyridinium chloride (CPC) and cetrimide enhanced the lipophilicity of adefovir 136- and 87-fold, respectively. The apparent permeability of adefovir in combination with CPC (counter-ion) was 2.5-fold greater than ADV permeability in the PAMPA model. The apparent permeability of adefovir-CPC (counter-ion) was 1.3-fold greater than that of adefovir dipivoxil permeability in a biologic membrane (everted gut sac). Conclusion: These results suggest that the adefovir-CPC ion-paired system has potential for improving the permeation of adefovir across the intestinal membrane.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.